Intra-household consumption inequality: empirical evidence from Brazil - Velilla Gómez, Raúl Alfonso (2017)
The analysis of inequality has been traditionally based on measures of income at the household level, ignoring the distribution of resources within the household. In fact, the traditional analysis of inequality had been based on the unitary model of consumer behavior, which assume an equal distribution of resources among family members. In doing so, important aspects as gains from joint consumption, that could influence individual well-being, are not taken into account. This drawback has occurred because typical micro-data on consumption usually provide information at the household level instead of at individual level, making it impossible to obtain direct measures of inequality based on individual consumption. Brazil is not an exception on this issue and the analysis of how the intra-household resource allocation process is given has not received much attention and remains a puzzle. In order to fill this gap, this research apply a collective consumption model to analyze economic inequality among individuals of Brazilian families. To achieve this, we identify the so-called resource shares, which are considered useful measures of individual consumption expenditure and can be estimated directly from household level data. In particular, we identify each member’s share of total household consumption through his or her expenditure on a private assignable goods such as clothing and footwear. Therefore, we are able to recover information about the economic well-being of household members. This study used micro-level dataset from the Consumer Expenditure Survey (POF 2008/2009) collected by the Brazilian Institute of Geography and Statistics (IBGE). Our analysis has focused on traditional families, married couples with zero to three children. Our empirical results reveal the existence of inequality in the allocation of resources inside the household. In particular, we found that in Brazilian families men absorb a higher fraction of family resources than women in all family sizes. We also found that the share of total resources devoted to children increases with the number of children, but the average per child share decreases. In addition, our results suggest that adults’ education level seems to be associated to a larger of his or her fraction of the total expenditure, but is negatively related with resources of her or his partner. Our finding reveal a positive effect of women’s participation in the labor market and her education level with the shares devoted to their children. Furthermore, our results identify a possible heterogeneity in the allocation of resources inside the household across regions. In particular, we found that families located in Southeast and Northeast regions seems to distribute their resources more equally among their members compared to the other regions. In general, our results did not reject the collective model in all estimations. By contrast, we do reject the standard unitary model. Finally, our results are informatively crucial for the design of redistributive policy or social programs, because they provide a broader and more accurate view of the well-being of individuals. More precisely, they could inform policy makers about how to target individuals effectively within households in order to minimize the incidence of inequality as well as provide useful information for Conditional Cash Transfer programs (such as Bolsa- familia) on how to address the transfers more efficiently.